PENGEMBANGAN APLIKASI MANAJEMEN DATA BUKU MENGGUNAKAN APLIKASI VISUAL STUDIO CODE DENGAN FRAMEWORK LARAVEL - Adinda Puteri Manisha; Efmi Maiyana (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2025)
Book data management in libraries and bookstores often faces challenges related to efficiency, accuracy, and speed in recording and searching for information. Manual systems still used in many places tend to be slow, error-prone, and impractical in data processing. Therefore, a software-based solution is needed that can support the digitization of the book management process. This study aims to develop a book data management application using Visual Studio Code as the development environment and the Laravel framework as the backend basis. The research method used is Research and Development (R&D) with a prototyping approach, which involves the stages of needs analysis, design, implementation, testing, and evaluation and revision. The results show that the application is able to simplify the process of recording, editing, deleting, and searching for book data efficiently. The designed interface is responsive and easy to use, so it can be operated by users with diverse technical backgrounds. System testing achieved a success rate of up to 95% in terms of functionality and data accuracy, confirming that the use of Laravel in book management application development makes a significant contribution to increasing the productivity, security, and effectiveness of book data management.